Managerial and Accounting Training for Professionalism Development of Village-Owned Enterprises: - - Priyatiningsih, Katharina; Susilawaty, Riauli; Gunawan , Arwan (Training & Research Institute - Jeramba Ilmu Sukses, 2025)
Part of the village's wealth is managed as assets through business entities called BUMDes with the products produced being goods and services to meet the needs of village communities, so BUMDes is often referred to as a new approach to mobilize and improve the economy of village communities based on the potential and needs of the village. The general aim of BUMDes Sariwangi, Parongpong District, West Bandung Regency is to improve the village economy, improve community businesses, create opportunities and market networks that support the public service needs of residents, improve community welfare through improving public services, as well as for economic growth and equality which leads to income. village communities and village original income. BUMDes requires human resources with high qualifications and professionalism to overcome challenges, be adaptive, and provide services to the community. The issue of managerial and accounting abilities becomes the focus in solving problems that arise due to a lack of education level and understanding of professionalism at work. Developing professionalism through creativity, innovation, and responsiveness into the concept of understanding skills in managerial and accounting training is expected to bring BUMDes Sariwangi to develop more professionally as a business organization in rural areas. The results show that after training, managerial and accounting abilities have improved, and professionalism has developed.